Conquering amide planarity: Structural distortion and its hidden reactivity. Issue 13 (28th March 2018) - Adachi, Shinya; Kumagai, Naoya; Shibasaki, Masakatsu
Graphical abstract: Highlights: Recent advances in amide N–C(O) bond activation are reviewed. Brief historical overview of distorted amides is summarized. Reactive amides are categorized based on structures and reviewed systematically. Abstract: Amides are generally considered as a low-reactive chemical entity among the carbonyl group, and therefore fewer opportunities to be involved in catalytic transformations as substrates. The origin of the stable nature of amides is resonance stabilization in the planar structure, which has drawn considerable attention from organic and physical chemists, leading to the discovery of distorted amides that exhibit a substantially reactive nature. Recent focus in this field is on the catalytic transformation of designed amides with moderate distortion or reduced resonance stabilization. This digest reviews the brief history of the quest for highly distorted amides and introduces a collection of recent studies on catalytic transformations of designed amides.